New Media, First Time Voters and the 2007 Australian Federal Election - Howell, Gwyneth and Da Silva, Bruce (Public Communication Review, 2010)
Researchers suggest that the youth of today has disengaged from the political landscape in Australia. However, the online realm provides potential first time voters an avenue in which to engage in politics in an environment that is generally associated with a youthful demographic. New media tactics utilised during the 2007 Australian federal election aimed to not only attract youthful voters, but also to educate and deliver policy on a level generally associated with the 18-24 demographic. This study explored the effectiveness of new media in the political communication context, in particular with relation to first time voters. This research found that first time voters were not as engaged as predicted, and that the third party sites were more popular with undecided voters than the formal political party sites in voter influence.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTEzMC9wY3IudjFpMS4xMjg4